(untitled) (Asian Journal of Medical and Biological Research, 2016)
The work has been designed to investigate the utilization of milk for consumption of fluid milk and milk products, their distribution pattern, pricing, shelf life and consumers preference of Mymensingh municipality in Bangladesh. The study was based on milk and milk products and data were collected from the selected sweetmeat shops by direct interview, of which 20 samples were collected from sweetmeat shops and 7 from goalas. Both tabular and statistical methods were used for collected data analysis. Shopkeepers of different sweetmeat shops received raw milk from farmers (52.6%) and goalas (47.4%) and the highest amount of whole milk was required in per unit production of rasomalai (21%) and ghee (18%) whereas the lowest amount in chomchom (9%). Milk products prices were not remained same throughout the year in this municipality due to fluctuation of raw milk availability and their price. Eid, Puja festivals and other educational activities results that may increase milk products selling especially rasogolla and kalojam. Research findings also showed non-significant difference in case of pricing, distribution pattern, shelf life and selling of milk and milk products following sweetmeats. Asian J. Med. Biol. Res. June 2016, 2(2): 266-273